1994
DOI: 10.1002/jnr.490370608
|View full text |Cite
|
Sign up to set email alerts
|

Met5‐enkephalin is localized within axon terminals in the subfornical organ: Vascular contacts and interactions with neurons containing gamma‐aminobutyric acid

Abstract: Met5-enkephalin inhibits sodium and water excretion and antagonizes the central actions of angiotensin II in subfornical organ of rat brain. We examined the ultrastructural basis for enkephalin modulation in this circumventricular region. Additionally, we examined the possibility that there might be cellular sites for functional interactions involving Met5-enkephalin and gamma-aminobutyric acid (GABA), a known inhibitory transmitter throughout the central nervous system. Met5-enkephalin and GABA were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…2). In the scant enkephalinimmunoreactive neuronal perikarya, a few large densecore vesicles are immunoreactive for enkephalin (Pickel and Chan, 1994); neither the sparse immunogold labeling for GABA (Pickel and Chan, 1994) nor the diffuse labeling for angiotensin II (Pickel et al, 1986) revealed any preferential cellular location. It should be noted that there are subjectively assessable quantitative differences in these attributes, even in animals that have not been subjected to any experimental procedure.…”
Section: Neurons Neuronal Perikaryamentioning
confidence: 88%
See 2 more Smart Citations
“…2). In the scant enkephalinimmunoreactive neuronal perikarya, a few large densecore vesicles are immunoreactive for enkephalin (Pickel and Chan, 1994); neither the sparse immunogold labeling for GABA (Pickel and Chan, 1994) nor the diffuse labeling for angiotensin II (Pickel et al, 1986) revealed any preferential cellular location. It should be noted that there are subjectively assessable quantitative differences in these attributes, even in animals that have not been subjected to any experimental procedure.…”
Section: Neurons Neuronal Perikaryamentioning
confidence: 88%
“…Other neurotransmitters and neurohormones that have been detected biochemically in the SFO (for citations, see Palkovits, 1987;Summy-Long, 1987) include acetylcholine, gamma-aminobutyric acid (GABA), noradrenaline, dopamine, histamine, serotonin, luteinizing hormone releasing hormone (LHRH), thyrotropin releasing hormone (TRH), somatostatin (SST), vasopressin (AVP), oxytocin, enkephalin, dynorphin, substance P, and motilin, but have so far escaped histochemical or immunohistochemical detection in neuronal perikarya. Enkephalin labeling has been reported in only a few neuronal perikarya (Wamsley et al, 1980) and may be colocalized with labeling for GABA (Pickel and Chan, 1994).…”
Section: Neurons Neuronal Perikaryamentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbit antiserum raised against methionine 5 ‐ENK has been previously characterized for cross‐reactivity against several members of the opioid family of peptides (Pickel and Chan,1994; Velley et al,1991). Immunodot blots showed that the antiserum principally recognized methionine 5 ‐ENK except at high concentrations (1:2,000), where there was cross‐reactivity with Leu 5 ‐ENK (Larsson1981; Velley et al,1991).…”
Section: Methodsmentioning
confidence: 99%
“…The rabbit antiserum raised against methionine 5 -ENK has been previously characterized for cross-reactivity against several members of the opioid family of peptides (Velley et al, 1991;Pickel and Chan, 1994). Immunodot blots showed that the antiserum principally recognized methionine 5 -ENK except at high concentrations (1:2,000) where there was crossreactivity with Leu 5 -ENK (Larsson 1981;Velley et al, 1991).…”
Section: Specificity Of Antiseramentioning
confidence: 99%